Molecular and pharmacological characterization of biogenic amine receptors from the diamondback moth, Plutella xylostella. Issue 10 (31st May 2021) - Liu, Tiansheng; Zhan, Xue; Yu, Yuan; Wang, Shaozhen; Lu, Cong; Lin, Guifang; Zhu, Xiangyu; He, Weiyi; You, Minsheng; You, Shijun
Abstract: BACKGROUD: Insect biogenic amines play important roles in mediating behavioral and physiological processes. They exert their effects by binding to biogenic amine receptors (BARs), which are specific receptor proteins in the G‐protein‐coupled receptor superfamily. BAR genes have been cloned and characterized from multiple model insects, including Drosophila melanogaster, Anopheles gambiae, Bombyx mori, Apis mellifera and Tribolium castaneum . However, relatively little work has addressed the molecular properties, expression profiles, and pharmacological characterization of BARs from other insects, including important pests. RESULTS: In this study, we cloned 17 genes encoding putative biogenic amine receptor proteins from Plutella xylostella, a global pest of Brassica crops. These PxBAR genes were five octopamine receptors (PxOA1, PxOA2B1, PxOA2B2, PxOA2B3, and PxOA3), three tyramine receptors (PxTAR1A, PxTAR1B, and PxTAR2), four dopamine receptors (PxDOP1, PxDOP2, PxDOP3, and PxDopEcR), and five serotonin receptors (Px5‐HT1A, Px5‐HT1B, Px5‐HT2A, Px5‐HT2B, and Px5‐HT7 ). All PxBARs showed considerable sequence identity with orthologous BARs, and phylogenetic analysis clustered the receptors within their respective groups while preserving organismal evolutionary relationships. We investigated their molecular properties and expression profiles, and pharmacologically characterized the dopamine receptor, PxDOP2. CONCLUSIONS: Our study provides important information and resources on biogenic amine receptors from P. xylostella, which suggests potential target sites for controlling this pest species. © 2021 Society of Chemical Industry. Abstract : In this study, molecular properties and expression patterns of 17 biogenic amine receptors from Plutella xylostella were analyzed. PxDOP2, an invertebrate‐type dopamine receptor, was also pharmacologically characterized.